The Sacred Elixir: Christian Biblical Wine for Holy Communion - Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2024)
This comprehensive examination delves into the diverse definitions and applications of wine, interweaving scientific, biblical, and cultural perspectives to contextualize its significance within the Christian sacrament. Exploring the chemical, microbiological, oenological, geographical, and physicochemical facets of wine, the study provides a nuanced understanding of its multifaceted nature. Scientific inquiry illuminates the myriad uses of wine, ranging from culinary and biomedical contexts to analytical chemistry and environmental considerations. The discourse extends to the symbolic depth of red wine, theological perspectives, and the pivotal role wine plays in both the Old and New Testaments. Notably, the viewpoints of evangelical theologians are meticulously examined, culminating in a poignant exploration of the sacred communion ritual, particularly its profound relevance for individuals in their final moments. This examination transcends the traditional confines of wine analysis, intertwining its scientific complexities with the spiritual and cultural dimensions encapsulated in biblical narratives. The symbolic richness of wine emerges as a common thread, connecting its chemical composition to profound theological implications. The discerning gaze of evangelical theologians further enriches the discourse, shedding light on the theological nuances surrounding wine within the Christian tradition. Finally, the exploration culminates in a poignant consideration of the sacred communion, offering profound insights into its transformative significance, particularly when administered to individuals nearing the culmination of their earthly journey. Fundamentally, this inquiry reveals the intricate interplay of meanings intricately woven into the essence of wine. It goes beyond the mere material substance, encapsulating a symbolic resonance that extends across the domains of science, spirituality, and culture.